The Contribution of Islamic School Culture and Teacher Role Modeling to Students’ Moral Character Formation Di MTs Unggulan Kota Probolinggo - Ludfi robiatul adawiyah; Sunarsih; Fatoni Aziz; Muhammad Alfi Syahrin (Educational Research Center, 2026)
This study aims to analyze the influence of teacher examples and Islamic school culture on the formation of students' moral character in MTs Unggulan Tunas Bangsa. This study uses a quantitative approach with the type of associative research. The research population is all students of MTs Unggulan Tunas Bangsa which totals 80 students. The research sample was determined using the proportional random sampling technique and calculated with the Slovin formula at an error rate of 5%, so that 44 respondents were obtained. Data collection was carried out using a five-point Likert scale questionnaire. Data analysis was carried out through normality tests, simultaneous tests (F tests), and determination coefficients (R²) with the help of the SPSS version 25 program. The results of the study show that Islamic school culture has a positive and significant effect on student morale. In addition, the example of teachers and Islamic school culture simultaneously had a significant effect on student morale with an F score of 16.384 and a significance of 0.000 < 0.05. The value of the determination coefficient (R Square) of 0.444 showed that the two independent variables were able to explain 44.4% of the variation in student morale, while the remaining 55.6% were influenced by other factors outside the study.